Effect of Zr on inclusions and microstructure of non-quenched and tempered steel F38MnVS - Yucheng Wang; Yang Li; Zhouhua Jiang; Meng Sun; Shuai Ma; Yunqie Mao; Yanshuo Ma; Tianci Li; Dengyunfei Nie; Rui Yang (Journal of Materials Research and Technology)
To examine the influence of Zr on the inclusions and microstructure of non-quenched and tempered F38MnVS steel, optical microscopy (OM), scanning electron microscopy (SEM), high-temperature laser confocal microscopy (HT-CLSM), transmission electron microscopy (TEM), and thermodynamic calculations among others are utilized. The obtained results reveal that adding Zr could alter the inclusions from Al2O3 to ZrO2, and ZrN appears with the increase of Zr content. Additionally, 220 ppm Zr exhibits the best impact on the inclusion size, reducing the average diameter of the inclusions from 5.04 μm to 2.87 μm. At the same time, the addition of Zr causes the austenite grain size to decrease and more intragranular ferrite appears. By appropriately evaluating the Zener pinning force, the Zener pinning force of the experimental group with a Zr content of 220 ppm is obtained as 0.034 J/mol, which possesses a more pronounced pinning effect on the austenite grain boundaries compared with 0 ppm Zr. By evaluating the mismatch degree, the mismatch degree between ZrO2 and α-Fe is predicted to be 6.9%, so it can be utilized as an effective heterogeneous nucleation core to induce α-Fe nucleation. In conjunction with the manganese-depleted zone theory, both of them jointly promote the nucleation of α-Fe. The findings of this study can serve as a fairly solid basis for using Zr treatment in the preparation of non-quenched and tempered steel for automotive applications.